Relationship Between the Concentration of Mercury (Hg) Along Kahayan Watershed Central Kalimantan with the Bioaccumulation, Morphological and Cytological Changes of Catfish (Pangasius pangasius) - Savitri, Shanty; Ghofur, Abdul; Amin, Moch. (Proceeding International Conference on Global Resource Conservation, 2013)
Kahayan River is known to be polluted by mercury due to the gold mining activities which use the mercury in the amalgamation (gold purifying) process. The water and fish in this river are consumed by most of the community live in the river basin. The fish consumed by Central Kalimantan people generally come from Kahayan River. Catfish (Pangasius pangasius) is one of the fish which is often consumed by Central Borneo people. They like the fish because of its delicious taste and its fat flesh. Besides, the fish bones are quite big and do not reach its body flesh. Generally, the yellowtail catfish is also raised by the local citizen inside baskets called karamba along the Kahayan watershed. The purposes of this research are to know: 1) the connection between the concentration of mercury along the Kahayan watershed and the mercury bioaccumulation contained in the catfishâs gill, liver, kidney, and muscles, 2) the catfishâs morphological changes related to the mercury bioaccumulation, and 3) the catfishâs cytological changes related to the mercury bioaccumulation. The results of the research are 1) there is connection between the mercury concentration along the Kahayan watershed and the mercury bioaccumulation contained in the catfishâs gill, liver, and muscles or Ho acceptance, 2) the morphological changes in the fishâs organs are: (a)the gill are experiencing colour changes from red with no spot into pink with spots, (b) theÂ catfishâs liver are experiencing colour changes from brownish into dark red, and shape changes from compact and not wrinkled into a little bit wrinkled, (c) the fishâs kidney are experiencing colour changes from red into dark brownish red, and shape changes from oval into wrinkled, (d) the fishâs muscles are not experiencing morphological changes either the colour or the shape, there are only some spots in the middle part of the muscle, 3) the cytological changes in the organs cells of the catfish are: (a)the changes in the gillâs cells are in the form of lamella edge swelling, lamella epitheliumÂ cell spreading, and nucleus disappearing; these indicate that there is necrosis in the gillâs cells; (b) the necrosis in the heart cells are marked with the cells colour absorption as the consequence of cells permeability declining and oedema (cell swelling); (c) the necrosis in the kidney cells are marked with the cells colour absorption as the consequence of cells permeability declining and oedema (cell swelling); (d) the cytological changes in the muscles cells of the catfish are not clearly seen, but the blood smear of the sample fish from the villages whose river water indicated to be polluted by mercury like Tumbang Anjir village is having necrosis, indicated by a strong colour absorption as the consequence of cells permeability decliningFrom the research results, it can be concluded that the mercury bioaccumulation in the Kahayan watershed related to the catfishâs morphological and cytological changes is as the result of the toxic nature of mercuryand there is direct connection between the mercury concentration along the Kahayan watershed and the mercury bioaccumulation inside the catfishâs body.Â Keywords: bioaccumulation, catfish, cytological change, mercury, morphological changeÂ